Conselho escolar: uma avaliação da política de gestão democrática escolar na rede pública municipal de Aquiraz - Rodrigues, Maria Djacira de Souza (2025)
This research aims to evaluate the performance of the School Councils of Aquiraz, considering their possibilities and difficulties still encountered in the consolidation of this space within schools, analyzing the contribution of managers to the implementation of democratic management in municipal public schools, understanding the context and content of the School Council Policy, investigating their trajectories and seeking to evaluate the performance of councilors in the temporal cut of 4 years (2021-2024) and territorial, considering the municipality of Aquiraz. School Councils are institutional spaces constituted by different actors: parents, students, teachers, managers and employees who deal with various educational matters and seek collective decision-making, aiming at the quality of teaching and learning outcomes. If we consider the fundamental contribution of public schools to the construction of participatory citizenship and take it as a permanent and collective construction, we will see that school councils are fundamental in schools. This research is characterized by the qualitative approach in its typology, in which we use bibliographic, documentary and field research; and the in-depth evaluation of the policy proposed by Rodrigues (2008). The theoretical construction is supported by authors such as: (Gohn, 2002, 2019; Soares 2013; Paro 2001, 2017; Veiga, 1995; Vieira, 2003, 2007; Luck, 2012; Libâneo, 2004; among others. Data collection was carried out through questionnaires with principals as a diagnostic form, serving as a basis for choosing the schools to be researched. The research's target audience is the managers and members of the school board of six schools. 03 (three) schools with defined actions to strengthen their boards (e.g.: member training, participatory planning, transparency in decisions, monthly meetings) and 03 (three) schools without structured practices to strengthen their boards (e.g.: inactive boards, lack of community participation, absence of planning). The comparison between schools with and without defined actions to strengthen their boards allows us to identify good practices and challenges, contributing to the formulation of more effective public policies and management strategies. To this end, semi-structured interviews and focus groups were conducted. As a result, we can see that there is recognition of the importance of School Councils, however there is still misinformation regarding their attributions, lack of knowledge of the municipal law that governs School Councils and lack of knowledge of the real role of the council in democratic management. The research revealed a considerable amount of legislation, however the effective functioning of the councils still depends on the awareness of the management groups. The main difficulties presented were the time available for meetings and lack of training of the councilors. The positive points presented are the creation of the council, the acceptance that they need to improve their performance, the recognition of the importance of the councils meeting more frequently and learning more through ongoing training on legislation, functions and attributions. Training plays a fundamental role in the attempt to correct the flaws in the implementation of the policy. In short, the research broadened the vision of a policy that has faced and continues to face difficulties, but which promises the democratic construction of education.